Deciphering the genetic basis of grain iron and zinc content in wheat under heat and drought stress using GWAS - Sahana Police Patil; Hari Krishna; Narayana Bhat Devate; Karthik Kumar Manjunath; P. N. Vinodh Kumar; Divya Chauhan; Shweta Singh; Hanif Khan; Chandra Nath Mishra; Neelu Jain; Gyanendra Pratap Singh; Pradeep Kumar Singh (PLoS ONE, 2025)
Wheat, a crucial food crop, is inherently deficient in essential micronutrients such as iron and zinc. Climate change exacerbates its vulnerability to abiotic stresses like drought and heat. Developing varieties that are both climate-resilient and nutrient-dense offers a sustainable approach. The objective of this study was to identify genomic regions linked to grain Fe content (GFeC), grain Zn content (GZnC) and thousand grain weight (TGW) traits in wheat grains subjected to heat and drought stress through genome-wide association studies (GWAS). A genetically diverse set of 280 wheat genotypes was assessed across three conditions: timely sown, late sown (heat stress), and restricted irrigation (drought stress) over two years. Variation in iron and zinc levels among genotypes was significant among the conditions, with moderate heritability. Through GWAS 37 significant MTAs across the conditions were identified. For thousand grain weight (TGW) 12 MTAs, for grain Fe content (GFeC) 14 MTAs, and for grain Zn content (GZnC) 11 MTAs were detected. Notably, four MTAs for GFeC two of which were specific to heat stress were located on chromosome 7A. Among these, AX-94432820 (LSIR_23) resides near a RING-H2 finger protein gene involved in metal-ion binding. Additionally, the stable SNP AX-94953068, also on 7A, is adjacent to TraesCS7A02G171600, a gene implicated in stress response. For GZnC, the stable SNP AX-95001849 (r2 = 12.89%) was significant under both TSIR and TSRI, it maps to a plasma membrane ATPase. Using multivariate analysis, MGIDI scores were calculated, identifying nine genotypes that excelled for all three traits and conditions: RAJ4546, UP3063, HD3334, DBW296, MP1368, DBW333, UP3058, DBW332, and BRW3863. These findings will support biofortification breeding of the nutri-rich wheat varieties.